ELECTROPHYSICAL ASPECT OF DESTRUCTION OF ULTRA-DISPERSED DIAMOND SHELLS IN THE COATING OF ABRASIVE GRAINS OF DIAMOND-SPARK GRINDING TOOL - Yury GUTSALENKO; Cătălin IANCU (Fiabilitate şi Durabilitate)
The mechanism of inclusion in abrasive cutting of diamond grains of grinding wheels, before sintering with a bond, protected by a thin metal coating with the inclusion of hollow shell nanostructures of detonation synthesis diamonds, is considered. A scheme of thermophysical gradient loading of shells under the influence of an electric field is presented. Qualitatively substantiated the position on the intensification of the cutting process at the microlevel using the technological method of diamond-spark grinding and other approaches to machining with diamond-abrasive tools with their inclusion in the electrical circuit together with the cutting zone.